Nutritional management of obese patient with young hypertension and hyperlipidemia - Ying, C.Y.; Izzatul Safiah, K.; Amira Nadiah, A.B. (2021)
Assessment Mr. Y is 32 years old man. His weight is 113kg with a height of 186cm and body fat is 37.7%. He is under obese class 1 with BMI is 32.7kg/m2. His usual body weight is 72kg in November 2020. The biochemical data for total cholesterol, triglycerides, and low-density lipoprotein are high, 6.2, 1.9, and 4.3mmol/L respectively. The renal profile and full blood count are normal. The blood pressure is 170/105mmHg, at stage 2 hypertension with a pulse rate of 60 beats per/min. Mr. Y has an excessive estimated energy intake, 3197kcal/day@154`)/0 of estimated energy requirement, total estimated fat intake 96g/day@167°/0 of fat requirement, and estimated sodium intake 3953mg/day@197% of sodium requirement. He is at the preparation stage as he agrees to take action on the nutrition recommendations provided. Diagnosis The diagnoses are excessive energy intake (NI-1.3), excessive fat intake (NI-5.5.2), excessive mineral intake (sodium) (NI-5.10.2) related to food and nutrition-related knowledge deficit concerning energy, fat, and sodium intake as evidenced by intake of excessive estimated energy intake 3197kca1/day@ 154% of estimated energy requirement, estimated fat intake 96g/day@167% of estimated fat requirement, and estimated sodium intake 3953mg@197% of sodium requirement. Intervention The main objective is to reduce body weight by 0.5-1kg/week, to attain and maintain the blood pressure as close as normal range <120/80mmHg, and to normalize fasting serum lipid profile as close as normal range, meanwhile, the long-term goals are to achieve healthy body weight at normal BMI and to prevent further complications of hyperlipidemia and hypertension such as heart disease and stroke. The plan is to educate on a weight reduction diet, low fat and cholesterol diet, low salt diet and promote physical activity. Monitoring & Evaluation To review and monitor the body weight, lipid profile, blood pressure, dietary intake, and compliance.